2003
DOI: 10.1016/s0896-6273(03)00597-x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Population Code for Working Memory in the Prefrontal Cortex

Abstract: Some neurons (delay cells) in the prefrontal cortex elevate their activities throughout the time period during which the animal is required to remember past events and prepare future behavior, suggesting that working memory is mediated by continuous neural activity. It is unknown, however, how working memory is represented within a population of prefrontal cortical neurons. We recorded from neuronal ensembles in the prefrontal cortex as rats learned a new delayed alternation task. Ensemble activities changed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
264
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(297 citation statements)
references
References 34 publications
25
264
3
Order By: Relevance
“…However, PL-IL lesions do not produce a deficit in working memory for a food reward (DeCoteau et al, 1997;Ragozzino & Kesner, 1999). Further support of this conclusion was reported by Chang, Chen, Luo, Shi, and Woodward (2002), who found sustained neural firing in the PL-IL cortex during the delay within a delayed matching-to-position task, and Baeg et al (2003) who recorded from the PL-IL cortex in a spatial delayed alternation task reported an increase in neural firing during the delay period.…”
Section: Working Memory (Short-term Memory)mentioning
confidence: 59%
“…However, PL-IL lesions do not produce a deficit in working memory for a food reward (DeCoteau et al, 1997;Ragozzino & Kesner, 1999). Further support of this conclusion was reported by Chang, Chen, Luo, Shi, and Woodward (2002), who found sustained neural firing in the PL-IL cortex during the delay within a delayed matching-to-position task, and Baeg et al (2003) who recorded from the PL-IL cortex in a spatial delayed alternation task reported an increase in neural firing during the delay period.…”
Section: Working Memory (Short-term Memory)mentioning
confidence: 59%
“…These results are consistent with previous reports that showed anticipatory activity from the PFC in delayed working memory tasks. it is well documented that mPFC neurons in rats show sustained activity during the delay period of delay tasks [29,[39][40][41] . in nonhuman primates, the region responsible for working memory is mainly located in the caudal DLPFC [3] .…”
Section: Discussionmentioning
confidence: 99%
“…Previous research showed that neuronal activity in the PFC increases throughout the training of animals to remember past events and prepare for future behavior, suggesting that working memory is mediated by neuronal activity [29] . However, it is still unclear how working memory is encoded within the PFC population [29] .…”
Section: Introductionmentioning
confidence: 99%
“…The mesolimbic and mesocortical pathways, arising mainly from the ventral tegmental area and innervating the mesial parts of the limbic system, including the NAc, AM, HF, and prefrontal cortex, function in incentive motivational processes (1,(7)(8)(9). It has been reported that reward information is processed in the prefrontal cortex, AM, and ventral tegmental area (3,(23)(24)(25)(26)(27)(28), and spatial information is processed in the HF (5,29,30), both of which then converge on NAc neurons (10,11,15,19). The D1R-KO eliminated the prereward excitatory response in the NAc of mice, whereas the response during and after reward was unchanged.…”
Section: Discussionmentioning
confidence: 99%